NOTES ON THE SYSTEMATY OF SOLOMON ISLANDS' PLANTS AND SOME OF THEIR NEW GUINEA RELATIVES. XI - B. C. Stone; T. C. Whitmore (Research Center for Biology, 1970)
Preliminary to a revision of the Myrsinaceae of the British Solomon Islands, we have found it necessary to name and validate the two large undescribed species of Tapeinosperma Hook.f., diagnoses of which are given in this paper, in order that their names may be available for use in connection with studies of the phytogeography of the Solomon Islands.